2020
DOI: 10.1364/oe.28.004836
|View full text |Cite
|
Sign up to set email alerts
|

Backside absorbing layer microscopy: a universal relationship between physical thickness and reflectivity

Abstract: The Backside Absorbing Layer Microscopy (BALM) is a recently introduced surface imaging technique in reflected light with an unprecedented combination of sensitivity and lateral resolution, hence very promising for the development of imaging sensors. This requires to turn BALM images into quantitative measurements. The usual way to analyze reflectivity measurements is to compare the optical signal and a numerical model with many adjustable parameters. Here we demonstrate a universal relationship between the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…The BALM reflectivity R(e) finds a real or virtual minimum (e min , R min ) for a low value of |e min | because the thickness e gold of the gold layer corresponds itself to a reflectivity minimum. In these conditions, it was shown that the BALM reflectivity obeys a parabolic variation with the thickness e of the added layer, 91 with (e min , R min ) being the minimum of this parabola. The position and amplitude of the parabola, and hence the values of e min and R min , are very sensitive to many factors, including the exact composition of the BALM substrate, the aperture of the microscope, the wavelength or the spectrum of the light source, the spectral response of the camera, and the refractive index of the solvent and of the added layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The BALM reflectivity R(e) finds a real or virtual minimum (e min , R min ) for a low value of |e min | because the thickness e gold of the gold layer corresponds itself to a reflectivity minimum. In these conditions, it was shown that the BALM reflectivity obeys a parabolic variation with the thickness e of the added layer, 91 with (e min , R min ) being the minimum of this parabola. The position and amplitude of the parabola, and hence the values of e min and R min , are very sensitive to many factors, including the exact composition of the BALM substrate, the aperture of the microscope, the wavelength or the spectrum of the light source, the spectral response of the camera, and the refractive index of the solvent and of the added layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The key point is that the variation R ( e ) remains parabolic whatever the detail of all of the instrumental parameters. Based on this remark, the strategy proposed in ref was therefore not to try to precisely handle all of these parameters but to determine case-by-case the three parameters that govern the exact shape of the parabola. As long as the refractive index of the added layer remains constant, knowledge of the three parameters is sufficient to convert the measured reflectivity into quantitative thickness measurements.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations